Hubungan Intensitas Shalat Dhuha dengan Tingkat Kecemasan Ibu Rumah Tangga yang Mengalami Masalah Finansial - Lidya Fitrianingrum; Wigyo Susanto; Dwi Heppy Rochmawati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Housewives who face financial problems often feel high levels of anxiety. This is caused by various daily demands that arise, causing feelings of anxiety, worry, and restlessness. However, by performing the dhuha prayer regularly, housewives can find it easy to reduce anxiety while facilitating their fortune. This study aims to examine the relationship between the intensity of dhuha prayer and the level of anxiety in housewives who experience financial problems. This study was conducted in Morosari Village, RT 02 RW 05, Sayung District, Demak Regency, and used a cross-sectional method. Data were obtained through questionnaires that were distributed directly to 58 respondents who were housewives. The sampling technique used was total sampling, and data analysis was carried out using univariate and bivariate tests, using the Spearman correlation test for bivariate analysis. The results of the univariate analysis showed that most respondents, as many as 23 people (39.7%), rarely performed the dhuha prayer. In addition, the highest level of anxiety occurred in 27 respondents (46.6%) who were classified as experiencing severe anxiety. Most of the respondents were in the age range of 40-50 years, as many as 27 people (46.6%). Bivariate analysis with Spearman correlation test showed that there was a significant relationship between the intensity of dhuha prayer and the level of anxiety in housewives who experienced financial problems, with a significance value of 0.000.